New Forms of Religious Life and Civil Society in Australia: Fragmentation or Enrichment? - Ireland, Rowan (Australian religion studies review, 2003)
Acts of religiously inspired terrorism have revived fears about the fragmentation of civil society as religious diversity increases in Europe, the USA and Australia. This article proposes criteria for distinguishing between types of religious associations which fragment civil society, thus confirming fears, and those that enrich it. In an exploratory study of six New Religious Movements (NRMs), two were considered closest to the type that enriches civil society. These two, Mahikari and Ananda Marga, are described and ways in which they contribute the enrichment of civil society are explored. Despite differences, the NRMs are found to enrich civil society not only as associations relating to other elements of local civil society, but also through the orientations and dispositions towards civic engagement they foster among members.